‘Harmonious’ Coexistence and Mutual Ignorance: Exclusivity in Religious Education in Indonesia - Hakam, Ahmad (Jurnal Studi Al-Qur'an, 2012)
Religious education and national interest often interrelate that its long process leads to an unpredicted outcome or side effects in the future. This paper seeks to analyse the unawareness between religious denominations, particularly Muslims and Christians in Indonesia which may be resulted by the religious education programmes and state policy involvement. A variety of literary sources is used to support the argument that religious harmony in Indonesia is not based on people’s self open-mindedness but more on the state authority’s strategy to advocate stability and coexistence between religions. Finally, it is suggested that the tolerance between religious communities should be motivated instead by a process of learning and acquiring knowledge of themselves and others by deepening their understanding of each and other’s faith. Keywords : Religious education, Indonesia, Religious harmony